RESPON PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L) DENGAN KOMBINASI PUPUK KANDANG DAN COCOPEAT PADA MEDIA PODSOLIK MERAH KUNING - Arianti, Selfi; Rosmalinda, Rosmalinda; Fitry Ramanda, Rika (Journal of Agro Plantation (JAP), 2024)
Cocoa (Theobroma cacao L.) is one of the main national plantation commodities and is the country's foreign exchange earner. This research aims to determine the effect of red and yellow podzolic media given a combination of cow manure and cocopeat on the growth of cocoa seedlings. This research used a non-factorial completely randomized design (CRD) consisting of 4 treatments and 5 replications, there were 20 experimental units. Each replication consists of 3 samples so that the total number is 60 samples. The parameters observed were plant height (cm), stem diameter (mm), number of leaves (strands), root dry weight (g), and soil pH. The research data were analyzed statistically using analysis of variance (ANOVA). If the treatment has a real effect, then a further test is carried out using the Duncan Multiple Range Test (DMRT) at the 5% level. The results of the research showed that the application of a combination of cow manure and cocopeat to red and yellow podzolic soil media had a significant effect on the growth of cocoa seedlings in terms of plant height, stem diameter, number of leaves, root dry weight and soil pH. A dose of 150 g of cow manure and 150 g of cocopeat is the best treatment to increase the growth of cocoa seedlings with a plant height of 19.89 cm, stem diameter of 4.90 mm, number of leaves 14.47, root dry weight of 0.69 g and soil pH 6.72.